Les méthodes des enquêtes internationales et leurs fonctions politiques - Pons, Xavier (Mesure et Evaluation en Education, 2014)
Choosing the method at the basis of an international survey is not only a technical or a scientific issue since the method has deep political implications. This article analyses the political functions carried out by the method at the origin of the OECD’s PISA program through the particular national experience of France (1995-2008). Adopting the standpoint of a qualitative sociology of education policies, it shows that the political functions of the method are different according to the sequences of the policy process. During the conception of PISA at the international level, the method strongly contributes to formulate the problems that must be addressed, how and by who. During the implementation in France, the method is a powerful tool of social control. Concerning the reception of PISA in France, the method highly structures the national policy debate by predetermining the possible cognitive and political uses of the survey.
Publisher: Association des spécialistes de la mesure et de l'évaluation en éducation